KARAKTERISTIK FISIK VELVA PISANG-BLUBERI DENGAN VARIASI KONSENTRASI CMC - Yolandra Hibatullah Isnaini; Jariyah Jariyah; Ifwarisan Defri (Journal of Food Technology and Agroindustry, 2022)
Banana is one of the most popular fruits that contains high nutrition. However, banana is perishable or easily rotten; therefore, further processing is necessary. One of the products produced from raw banana ingredient is Velva. However, Velva that was formed from banana has rather unatrractive color, thus it's important to add another ingredient such as blueberries. Blueberries add nutritional value to the Velva since they contain Vitamin C and anthocyanins which can act as antioxidants and add on red-purplish color. The problem arises in the Velva manufacturing is the formation of unstable texture; therefore, CMC as a stabilizer is needed. This study aims to determine the physical characteristics of the produced Velva using the proportions of bananas and blueberries and the CMC concentrations. This study used a completely randomized design with two factored factorial patterns. Factor I was the proportion of bananas:blueberries (40:60, 50:50 and 60:40) and Factor II was the CMC concentrations (0.1, 0.3, and 0.5%). Each treatment was repeated three times. The data obtained were analyzed using SPSS ver. 26 with Duncan's advanced test level of 5%. The best treatment was obtained at the proportion of bananas:blueberries (40:60) and CMC concentrations of 0.5% with viscosity criteria of 162 mPas, melting time of 19.340 mins/10 g, overrun of 34.333% with color analysis of *L 27.472, a*43.207, b*0.817.